SAP Enterprise Architecture : a blueprint for executing digital transformation - Musukutwa, Sheunopa Chalmers (Apress L.P., 2022)
Does digital transformation ever stop? The answer is a resounding "no" and this book guides you in developing an SAP enterprise architecture that prepares you for constant technology changes. The book introduces enterprise architecture, the role it plays in executing successful business strategy, and its application in SAP. A detailed step-by-step guide teaches you how to utilize SAP Enterprise Architecture Designer to model the four key areas: business, data, landscape, and requirements. Executives will gain insight into the considerations that will aid them in building their digital transformation road map while remaining agile to adapt to unforeseen circumstances. and adapting to the new normal. SAP partners and consultants will find their place in SAP's future. By the end of this book, you will learn what SAP enterprise architecture is and how to develop it along with its best practices. You Will Understand The fundamentals of enterprise architecture SAP enterprise architecture How SAP Enterprise Architecture Designer helps your enterprise Business, information, and infrastructure architecture Enterprise architecture best practices How enterprise architecture can prepare your business for the future Who This Book Is For Executives who currently run SAP implementations or are considering SAP implementations, SAP partners and consultants along with aspiring SAP consultants, and technology enthusiasts interested in understanding and articulating IT and business alignment through enterprise architecture